Dynamic Biomolecular "Mask" Stabilizes Zn Anode. Issue 26 (27th May 2022) - Li, Yanmei; Wang, Yingyu; Xu, Yuan; Tian, Wenhuai; Wang, Jiawei; Cheng, Liwei; Yue, Honglei; Ji, Runa; Zhu, Qiaonan; Yuan, Hao; Wang, Hua
Abstract: Zn anode is confronted with serious Zn dendrite growth and water‐induced parasitic reactions, which severely hinders the rapid development and practical application of aqueous zinc metal batteries (AZMBs). Herein, inspired by sodium hyaluronate (SH) biomolecules in living organisms featured with the functions of water retention, ion‐transport regulation, and film‐formation, the SH working as a dynamic and self‐adaptive "mask" is proposed to stabilize Zn anode. Benefiting from the abundant functional groups with high hydrophilicity and zincophilicity, SH molecule can constrain active water molecules on the Zn‐electrolyte interface and participate in Zn 2+ solvation structure to suppress parasitic reactions. Furthermore, the dynamical adsorption of SH with high‐density negative charge on the Zn surface could serve as Zn 2+ reservoirs to guide uniform Zn deposition. Consequently, stable Zn plating and an ultrahigh cumulative plating capacity (CPC) of 4.8 Ah cm ‐2 are achieved even at 20 mA cm ‐2 (20 mAh cm ‐2 ) in a Zn||Zn symmetric battery, reaching a record level in AZMBs. In addition, the Zn||β‐MnO2 full battery exhibits a substantially improved cycle stability. This work presents a route to realize a highly reversible and stable Zn metal anode by learning from nature. Abstract : A bimolecular "mask" is proposed to stabilize Zn anode. The dynamically adsorbed sodium hyaluronate "mask" on the Zn surface works as a protective barrier and Zn 2+ ion reservoir to mitigate parasitic reactions and induce homogeneous Zn deposition. Both the ultrahigh cumulative plating capacity of Zn||Zn battery and substantially improved cycle stability of Zn||β‐MnO2 battery are achieved.